2023
DOI: 10.1021/acs.jproteome.2c00603
|View full text |Cite
|
Sign up to set email alerts
|

MSstatsShiny: A GUI for Versatile, Scalable, and Reproducible Statistical Analyses of Quantitative Proteomic Experiments

Abstract: Liquid chromatography coupled with bottom-up mass spectrometry (LC-MS/ MS)-based proteomics is a versatile technology for identifying and quantifying proteins in complex biological mixtures. Postidentification, analysis of changes in protein abundances between conditions requires increasingly complex and specialized statistical methods. Many of these methods, in particular the family of open-source Bioconductor packages MSstats, are implemented in a coding language such as R. To make the methods in MSstats acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…For more complex designs we recommend MSstats, which can model a variety of experimental designs in a statistically rigorous manner. 55 We found that imputation can identify new quantitative peptides (Figure 5). As modern proteomics techniques increase the number of identifications, it is important to remember that not all of the detected peptides are quantitative.…”
Section: Discussionmentioning
confidence: 93%
“…For more complex designs we recommend MSstats, which can model a variety of experimental designs in a statistically rigorous manner. 55 We found that imputation can identify new quantitative peptides (Figure 5). As modern proteomics techniques increase the number of identifications, it is important to remember that not all of the detected peptides are quantitative.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it would be great to assess further if machine learning models can be trained on lower-level data as peptides are the most sensible unit and imputation on protein groups level performs one form of implicit imputation at the peptide level 8 . One could assess if imputed features on lower-level data can be reaggregated to protein groups, e.g using ideas from Sticker and coworkers 43 or MSStats 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not include non-general imputation methods as e.g. provided by MSstats 44 or without reusable software 72 . We used KNN interpolation of replicates based on the HeLa cell line measurements being repeated over time.…”
Section: Other Imputation Approachesmentioning
confidence: 99%
“…The intensities were compared using LFQ (label-free quantification) values [80] with Perseus (version 2.0.11 [81]). Contaminants and reverse sequences were removed from the matrix and LFQ intensities were log2-transformed using Mstats [82]. Before ttest and visualization using a volcano plot, the missing values were replaced by imputation with the normal distribution for each column separately (default settings).…”
Section: Protein Co-ip and Analyses By Lc-ms/msmentioning
confidence: 99%